2022
DOI: 10.3390/polym14030481
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Hemp Fibres Reinforced Composites Using Thermoplastic Polymers as Matrices

Abstract: Hemp fibres used as a reinforcing agent and three polymeric matrices (polypropylene, bicomponent, recycled polyester) were used to obtain composite materials by needle punching and heat pressing. The influence of the hemp/matrix ratio and the nature of the matrix on the properties of the composites were analysed. The obtained composites were characterised by physical–mechanical indices, thermal analysis (thermogravimetry (TG), differential thermogravimetry (DTG) and Differential Scanning Calorimetry (DSC)), Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 57 publications
4
29
0
1
Order By: Relevance
“…[ 41 ] The onset temperature of hemp fiber epoxy composites ranged between 313 to 326°C, and offset temperature varied from 411 to 431°C. [ 42,43 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 41 ] The onset temperature of hemp fiber epoxy composites ranged between 313 to 326°C, and offset temperature varied from 411 to 431°C. [ 42,43 ]…”
Section: Resultsmentioning
confidence: 99%
“…The reason for the early degradation of prepared composites is the presence of hemicellulose and lignin of fiber. [41] The onset temperature of hemp fiber epoxy composites ranged between 313 to 326 C, and offset temperature varied from 411 to 431 C. [42,43] The onset temperature for neat epoxy resin starts from 338 C, and weight loss during this stage is about 80.66% because of the dilapidation of polymer chains of neat epoxy resin. It was found that hemp fiber/epoxy composites have lower onset and endset temperatures than neat epoxy resins, which suggests they are less thermally stable.…”
Section: Morphological Analysismentioning
confidence: 99%
“…They have concluded that 50 % by weight is the optimal value for hemp fiber-reinforced PP felts. The studies of Shahzad [30] and Stelea et al [31] have also focused on the characterization of hemp-PP felts by testing them as plates. Chen et al [32] have compared the mechanical performance of hemp-PP non-woven to bagasse-PP, kenaf -PP, and ramie-PP non-wovens.…”
Section: Macrostructure Of Natural Fibersmentioning
confidence: 99%
“…The thermoplastic composite has outstanding characteristics, which are different from the traditional thermosetting composite, such as high toughness, high strength, fast forming, and recyclability [ 13 , 14 , 15 , 16 , 17 , 18 ]. It is a new type of composite material with high performance, low cost, and environmental protection and becomes an ideal material for civil aircraft structure components manufacturing, which can reduce weight effectively and improve processing efficiency [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%